Неизвестная рукопись ранней редакции сатиры А. Ф. Воейкова «Дом сумасшедших» [An Unknown Manuscript of the Early Version of Alexander Voeikov’s Satire “Dom sumasshedshikh”] - Balakin, Alexei (Slavica Revalensia, 2018)
This article introduces to a wide scholarly audience a newly discovered manuscript of Alexander Voeikov’s (1779—1839) satirical poem Dom sumasshedshikh (The Madhouse). The author’s argument is that the discovery of this manuscript helps us to establish the exact date of the poem’s composition, 1814, and not 1817, as was previously thought. Reading the poem in context provides an additional proof for Alexei Balakin’s hypothesis, as the text of the satire refers to the polemics of the day on how to render Greek hexameter in Russian verse.